Changes in soil nutrients, vegetation structure and herbaceous biomass in response to grazing in a semi-arid savanna of Ethiopia - Tessema, Z.K.; de Boer, W.F.; Baars, R.M.T.; Prins, H.H.T. (Journal of arid environments, 2011)
The effect of grazing was studied on vegetation structure, herbaceous biomass, basal and bare ground covers, together with soil nutrient concentrations in two locations in an Ethiopian semi-arid savanna. The lightly grazed sites had significantly higher herbaceous diversity, total abundance, basal cover and aboveground biomass, and a lower percentage of bare ground compared with the heavy grazed sites. Grazing pressure had no effect on the density and number of woody species as well as on the proportion of encroaching woody species. The light grazing sites had higher organic carbon, phosphorus and exchangeable bases, and therefore a higher pH and higher electrical conductance, indicating an improved soil nutrient status compared with heavy grazing sites, mainly attributed to the higher basal cover and standing biomass at light grazed sites, and the export of nutrients through grazing and dung collection from the heavily grazed sites. There were significantly higher soil nutrients, species diversity, aboveground biomass and basal cover in the light grazing sites compared with heavy grazing sites. We concluded that changes in herbaceous vegetation, standing biomass and soil compositions are caused by interactions between grazing, soil and vegetation, and these interactions determine the transitions of semi-arid savannas. ► Lightly grazing had a higher herbaceous diversity, abundance, basal cover and biomass, and a lower bare ground than heavy grazing. ► Grazing pressure had no effect on the density and number of woody species, and on the proportion of encroaching woody species. ► Light grazing sites had higher soil nutrients due to higher basal cover and biomass than heavy grazing. ► Changes in herbaceous vegetation, standing biomass and soil compositions are caused by interactions between grazing, soil and vegetation. ► The interactions of vegetation and soil under influence of grazing determine the transitions of semi-arid savannas.